Exploring perceived effects from loss of PEPFAR support for outreach in Kenya and Uganda - Mary Qiu; Ligia Paina; Daniela C. Rodríguez; Jess A. Wilhelm; Ezinne Eze-Ajoku; Alexandra Searle; Henry Zakumumpa; Freddie Ssengooba; Caroline MacKenzie; Sara Bennett (BMC, 2021)
Abstract Introduction In 2015, the President's Emergency Plan for AIDS Relief undertook policy shifts to increase efficiencies in its programming, including transitioning HIV/AIDS funding away from low burden areas. We examine the impact of these changes on HIV outreach in Kenya and Uganda. Methods Qualitative data collection was conducted as a part of a broader mixed-methods evaluation. Two rounds of facility-level case studies and national-level interviews were conducted in Kenya and Uganda, with health facility, sub-national and central Ministry of Health staff, HIV clients, and implementing partners. Results In both countries, the loss of outreach support affected community-based HIV/AIDS education, testing, peer support, and defaulter tracing. Discussion Loss of external support for outreach raises concerns for countries' ability to reach the 90-90-90 UNAIDS target, as key linkages between vulnerable communities and health systems can be adversely affected. Conclusion Development partners should consider how to mitigate potential consequences of transition policies to prevent negative effects at the community level.